Pain Perception and Stabilometric Parameters in People With Chronic Low Back Pain After a Pilates Exercise Program: A Randomized Controlled Trial. Issue 2 (January 2016) - Patti, Antonino; Bianco, Antonino; Paoli, Antonio; Messina, Giuseppe; Montalto, Maria Alessandra; Bellafiore, Marianna; Battaglia, Giuseppe; Iovane, Angelo; Palma, Antonio
Abstract : Abstract: Various exercise interventions, such as Pilates exercises and traditional physical therapy methods, are employed to decrease low back pain (LBP). Nonspecific low back pain (NSLBP) is distinct from LBP, however, as the distribution of pain is restricted to the region between the costal margin and the inferior gluteal. The aim of our randomized controlled trial was to evaluate the effects of a program of Pilates exercises on pain perception and stabilometric parameters in patients with NSLBP. Thirty-eight participants were randomly allocated, using a 1:1 scheme, to either the experimental group (EG) or control group (CG). The EG completed a 14-week program of Pilates exercises, performed thrice per week under the supervision of an exercise specialist, while the CG was managed with a social program only. Measures of posturography and Oswestry Disability Index (ODI) for pain perception were obtained at baseline (T 0 ) and after the 14 weeks of intervention (T 1 ). Posturography measures improved for patients in the EG, with both eyes open and eyes closed ( P < 0.05). There were no statistical differences in posturography in the CG. ODI decreased significantly in both groups over the 14 weeks of the study protocol: EG, T 0, 13.7 ± 5.0 compared with T 1, 6.5 ± 4.0 ( P < 0.001); and CG, T 0, 10.7 ± 7.8 compared with T 1, 8.4 ± 7.8 ( P < 0.01). A greater extent of reduction in pain was achieved in the EG. The Pilates exercise program yielded improvements in pain and posturography outcomes. Our study also confirms the applicability of posturography in evaluating postural instability in patients with NSLBP. Due to our relatively small study group, future studies would be necessary to confirm our findings.